2018
DOI: 10.1155/2018/6197549
|View full text |Cite
|
Sign up to set email alerts
|

Taxi Driver’s Operation Behavior and Passengers’ Demand Analysis Based on GPS Data

Abstract: The existing research outputs paid less attention to the relationship between land use and passenger demand, while the taxi drivers' searching behavior for different lengths of observation period has not been explored. This paper is based on taxi GPS trajectories data from Shenzhen to explore taxi driver's operation behavior and passengers' demand. The taxi GPS trajectories data covers 204 hours in Shenzhen, China, which includes the taxi license number, time, longitude, latitude, speed, and whether passengers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Therefore, it is first necessary to associate the pick-up/drop-off locations with the buildings. Existing studies have found that the maximum walking distance of taxi passengers is approximately 300 meters; hence, we used this as the distance from the passenger's pick-up/drop-off location to the destination building and set the building buffer radius parameter as 300 meters [28][29][30], which is used to calculate the total number of pick-ups/drop-offs for the buildings within the range.…”
Section: Construction Of the Spatial-temporal Interaction Matrix Of Tmentioning
confidence: 99%
“…Therefore, it is first necessary to associate the pick-up/drop-off locations with the buildings. Existing studies have found that the maximum walking distance of taxi passengers is approximately 300 meters; hence, we used this as the distance from the passenger's pick-up/drop-off location to the destination building and set the building buffer radius parameter as 300 meters [28][29][30], which is used to calculate the total number of pick-ups/drop-offs for the buildings within the range.…”
Section: Construction Of the Spatial-temporal Interaction Matrix Of Tmentioning
confidence: 99%
“…After the community discovery algorithm based on multi-objective optimization solves the division model of the public bicycle scheduling area, the experimental results shown in Figure 5.6 are obtained. By comparison between Figure 5.4, the result shows that the sites along the Williamsburg Bridge and the riverside along Manhattan is divided into the same dispatch area, which is more n line with the rules of public bicycle rental and resolving the anomaly [27]. The difference between the number of sites and regional sites is too large [28].…”
Section: Resultsmentioning
confidence: 86%
“…It is well known that GPS does not efficiently function in tunnels and densely built up locations [38]. Likewise, some of the RFID tags may not be detected in very dense crowds, and the local sensor network may not be deployed in places with a lack of space.…”
Section: Radio Frequency Identification (Rfid) and Wireless Sensormentioning
confidence: 99%